Processing and interpretation of multichannel seismic lines acquired in the Drygalski Basin of the western Ross Sea, Antarctica - TENTI, MARTINA (Pisa University, 2019)
The present Master degree thesis work focused on the re-processing and interpretation of IT90AR60 and IT90AR61A-B multichannel seismic lines acquired in the western Ross Sea (Antarctica) in order to improve the above-mentioned seismic lines and realize a seismo-stratigraphic interpretation to enhance the comprehension of the Drygalski Basin evolution located in the western Ross Sea, Antarctica. Two kinds of multiple attenuation techniques were used: SRME and predictive deconvolution. The re-processed seismic lines were interpreted by tracing different horizons according to seismo-stratigraphic criteria. In particular, it was possible to recognise and date two erosional unconformities: the Unconformity B represents a huge Miocene hiatus (14.7-4 Ma) and the Unconformity T represents a more recent erosional event of Late Pleistocene (3 Ma). Four different units were recognised: Unit 4, Unit 3, Unit 2 and Unit 1. The Unit 4 could represent glacio-marine sediment sub-horizontally stratified except for some zones where it was intensively deformed and disrupted by faults; Unit 3 is characterized by discontinuous, irregular and chaotic reflectors, which show a downlap geometry from coast seaward above the basal unconformity B providing progradational features interpreted as ice-proximal sediment; Unit 2 shows seismic facies with chaotic and massive geometry and with blank zones, probably due to till sediments lenses occurring on the side of the basin; Unit 1 is characterized by locally distributed moraines occurring in the depocenter of the basin. Moreover, N-S oriented faults were traced and, some of these, were correlated between the two seismic profiles. Once the interpretation was completed, isobate and isopach maps were created in order to understand the shallow stratigraphy in depth of the Drygalski Basin and the thicknesses of the deposited units. In addition to this, morphobathymetric data were analysed by providing information about the evolution of the Antarctic Ice Sheet. In fact, it was possible to observe ...